Efficiency of lenalidomide, bortezomib and prednisone (RVP) in patients with newly diagnosed multiple myeloma - K. A. Belousov; T. A. Mitina; Yu. Yu. Chuksina; A. K. Golenkov; E. V. Kataeva; E. V. Trifonova; Yu. B. Chernykh; L. L. Vysotskaya; S. G. Zakharov; E. F. Klinushkina; A. N. Mitin (Онкогематология)
Objective: to study the efficacy and safety of the antitumor RVP program (lenalidomide, bortezomib, prednisone) as a first-line therapy in patients with multiple myeloma (MM). Materials and methods. A prospective study involved 39 patients with MM (15 women, 24 men), median age 61 years (30–76 years). All patients had Durie–Salmon stage III disease. According to the paraprotein isotype variant, 19 patients (48.7 %) had Gk myeloma, 8 (20.5 %) had Gλ, 4 (10.2 %) – Ak, 1 – Aλ, 1 – Dk, 1 – paraproteinemia Bens-Jones k and 1 – Bens-Jones λ, 2 – Dλ, and 2 patients – nonsecreting MM. The average level of plasma cells in the bone marrow was 31.7 % (0.8–80.0 %). In 14 (35.8 %) patients there were plasmacytomas of various localization (spine, cranial bones, clavicle, pleura). Nine (23.0 %) patients had renal failure, requiring the start of renal replacement therapy. The average Karnovsky index in the study group was 50 %. All patients received RVP therapy (lenalidomide 25 mg in 1–14 days, bortezomib 1.3 mg subcutaneously in 1, 4, 8, 11 days, prednisolone 60 mg/m2; the interval between courses was 42 days) as the first line therapy. Evaluation of therapy efficacy, characterized by overall survival, objective response rates (the number of complete, very good partial and partial remissions) was performed after 6 treatment courses. Results. The median follow-up was 15 months; the median of overall survival was not achieved. Objective antitumor response achieved in 29 (74.3 %) patients, including complete remissions in 3 (7.6 %), very good partial remissions – in 7 (17.9 %), partial remissions – in 19 (48.7 %) patients. In 2 out of 9 patients who received renal replacement therapy, independence from dialysis therapy was achieved. Cases of III–IV stage hematological and non-hematological toxicity in the study were not noted. Conclusion. The antitumor RVP program showed high efficacy and safety as a first-line therapy in a non-selective group of patients, including those with a complicated MM course.